Study of Online Impulsive Buying in Indonesia During Covid-19 Pandemic Outbreak - Muhartini Salim; Putri Oktaviany; Rina Suthia Hayu (APMBA (Asia Pacific Management and Business Application), 2021)
E-commerce has swipe the new culture of marketing way in Indonesia. During the Covid-19 pandemic the intensity of the uses of marketplace canal is increasing dramatically. This research aims to know the effect of Website Quality, Electronic Word-of-Mouth and Sales Promotion on Impulsive Buying behaviors of Shopee consumers during the Covid-19 pandemic outbreak in Indonesia. The type of research used in this research was quantitative research. Data was collected through the online questionnaire. By surveying 445 respondents that had done online shopping on Shopee e-commerce during the Covid-19 pandemic this study adopt non-probability sampling technique was used in this research with purposive sampling as a sampling method. Multiple Linear Regression with SPSS 21.0 For Windows was conducted to analyze the data collected from the online questionnaire. The findings revealed that Website Quality, Electronic Word-of-Mouth and Sales Promotion of Shopee significantly and positively affect public's Impulsive Buying in e-commerce Shopee during the Covid-19 Pandemic partially or simultaneously.